Prevalence of Work Related Psychological and Musculoskeletal Problems among Business Process Outsourcing Workers - Kanniappan, Vadivelan (J Lifestyle Med, 2020)
BACKGROUND: Musculoskeletal disorders are mainly caused due to static work which includes sitting and standing for a prolonged time and sedentary unhealthy lifestyle lead to physical related health problems and may affect one’s psychosocial, physical and mental health. The purpose of the study is find out the prevalence of work related psychological and musculoskeletal problems among business process outsourcing workers. METHODS: An observational study in which 100 participants were included according to the inclusion and exclusion criteria with 50 males and 50 females. Participants with age of 20-35 years and minimum 1 year of work experience with alternative working shifts were selected for the study. Stress and burnout questionnaire, Cornell musculoskeletal discomfort questionnaire and body mass index calculator were used as an outcome measure in the study. RESULTS: Musculoskeletal problem was higher in neck region and wrist region and 2% participants had burnout stress syndrome. CONCLUSION: High prevalence of musculoskeletal disorder found over neck region, hip/buttocks, wrist and low back and 2% of the population had burnout stress syndrome and no significance correlating body mass index and musculoskeletal disorder.